1995
DOI: 10.2175/106143095x131565
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of simazine: Ozone, ultraviolet, and combined ozone/ultraviolet oxidation

Abstract: A laboratory study was conducted to investigate the kinetics and byproducts of simazine oxidation by ozone, ultraviolet radiation (UV), and combined ozone and UV. Byproducts were identified by HPLC. Simazine was oxidized rapidly by ozone, UV, and ozone and UV. For example, 4 mg/L simazine disappeared completely after oxidation by 34 mg/min ozone at pH 7.2 for 15 minutes. Simazine disappearance rates during ozonation increased with applied ozone dose and pH. Dealkylation and dechlorination byproducts were forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 18 publications
1
24
0
2
Order By: Relevance
“…power. A laser microprobe analysis, using 266 nm laser light, Similarly, Lai et al [150] studied the photooxidation of was applied to study the photodegradation of atrazine (vide simazine (vide supra) by UV radiation in the presence and supra), propazine (vide supra) and simazine (vide supra) absence of O . Simazine disappearance increased with UV 3 [146].…”
Section: The Metalaxyl Hmethyl N-(2-methoxyacetyl)-n-(26-mentioning
confidence: 99%
“…power. A laser microprobe analysis, using 266 nm laser light, Similarly, Lai et al [150] studied the photooxidation of was applied to study the photodegradation of atrazine (vide simazine (vide supra) by UV radiation in the presence and supra), propazine (vide supra) and simazine (vide supra) absence of O . Simazine disappearance increased with UV 3 [146].…”
Section: The Metalaxyl Hmethyl N-(2-methoxyacetyl)-n-(26-mentioning
confidence: 99%
“…CA is formed by microbial degradation, 7-10 chemical oxidation, 11 and photooxidation 12,13 of parent triazine compounds. Héquet et al 12 demonstrated an efficient degradation of atrazine, the best known member of the group of triazine herbicides, during photolysis in a photoreactor or a photocatalytic system with titanium dioxide and a reduced range of irradiation.…”
Section: Cyanuric Acidmentioning
confidence: 99%
“…Dethylatrazine, deisopropylatrazine, and ch l o ro d i a m i n o -s -t riazine have been rep o rted as ozo n at i o n products with respective amounts of 36%, 16%, and 3% of the original atrazine unaccounted for after 10 min of treatment [28]. When a UV light source was coupled to the ozonation process, simazine degradation increased; the main degradation products were 2,4-diamino-6-hydroxy-s-triazine ( 3 6 % ) , 2 -a m i n o -4 , 6 -d i hy d ro dy -s -t riazine (13%), and cyanuric acid (10%) after 120 min of treatment [29]. After 11.5 h Cl release, in FR atrazine oxidation, accounted for 40% rep resenting dech l o ri n ated interm e d i ates while ch l o ro d ia m i n o -s -t riazine and 4-acetamide-6-amino-2-ch l o ro -s -t riazine roughly represented the sum of chloro-s-triazines byproducts (60%) [30].…”
Section: Triazinesmentioning
confidence: 99%